Role of grain boundaries in Ge–Sb–Te based chalcogenide superlattices. (21st March 2019) - Cojocaru-Mirédin, Oana; Hollermann, Henning; Mio, Antonio M; Wang, Anthony Yu-Tung; Wuttig, Matthias
Abstract: Interfacial phase change memory devices based on a distinct nanoscale structure called superlattice have been shown to outperform conventional phase-change devices. This improvement has been attributed to the hetero-interfaces, which play an important role for the superior device characteristics. However, the impact of grain boundaries (GBs), usually present in large amounts in a standard sputter-deposited superlattice film, on the device performance has not yet been investigated. Therefore, in the present work, we investigate the structure and composition of superlattice films by high resolution x-ray diffraction (XRD) cross-linked with state-of-the art methods, such as correlative microscopy, i.e. a combination of high-resolution transmission electron microscopy and atom probe tomography to determine the structure and composition of GBs at the nanometer scale. Two types of GBs have been identified: high-angle grain boundaries (HAGBs) present in the upper part of a 340 nm-thick film and low-angle grain boundaries present in the first 40 nm of the bottom part of the film close to the substrate. We demonstrate that the strongest intermixing takes place at HAGBs, where heterogeneous nucleation of Ge2 Sb2 Te5 can be clearly determined. Yet, the Ge1 Sb2 Te4 phase could also be detected in the near vicinity of a low-angle grain boundary. Finally, a more realistic view of the intermixing phenomenon in Ge–Sb–Te based chalcogenide superlattices will be proposed. Moreover, we will discuss the implications of the presence of GBs on the bonding states and device performance.